2020
DOI: 10.3390/ijms21145027
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 Protein Levels and Association to Response to First-Line Irinotecan-Based Therapy for Patients with Metastatic Colorectal Cancer

Abstract: In this study we investigated the use of cancer cell protein expression of ABCG2 to predict efficacy of systemic first-line irinotecan containing therapy in patients with metastatic colorectal cancer (mCRC). From a Danish national cohort, we identified 119 mCRC patients treated with irinotecan containing therapy in first-line setting. Among these, 108 were eligible for analyses. Immunohistochemistry (IHC) analyses were performed on the primary tumor tissue in order to classify samples as high or low presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the chemotherapeutics from nonsubstrates of ABCB1 may increase its mRNA expression [ 179 ]. Complementary to this, some tumor cells may also express other efflux transporters responsible for drug resistance, such as ABCG2 (breast cancer resistance protein, BCRP) [ 180 ] or ABCC1 (multidrug-resistance-associated protein 1, MRP1) [ 181 ]. That is why looking for new drugs with the potential to overcome drug efflux is an intensive challenge for experts from various fields.…”
Section: The Potential Of Agnps In Nano-oncologymentioning
confidence: 99%
“…Moreover, the chemotherapeutics from nonsubstrates of ABCB1 may increase its mRNA expression [ 179 ]. Complementary to this, some tumor cells may also express other efflux transporters responsible for drug resistance, such as ABCG2 (breast cancer resistance protein, BCRP) [ 180 ] or ABCC1 (multidrug-resistance-associated protein 1, MRP1) [ 181 ]. That is why looking for new drugs with the potential to overcome drug efflux is an intensive challenge for experts from various fields.…”
Section: The Potential Of Agnps In Nano-oncologymentioning
confidence: 99%
“…Both localizations were also detected by Hu J et al [ 24 ] in right-sided colorectal cancer tissues. Palshof et al [ 58 ] reported recently that in addition to the cytoplasm, ABCG2 expression was also present in both the apical/luminal and basolateral membranes of the colorectal cancer cells. It could be speculated that subcellular localization of the ABCG2 can be associated with specific function or loss of function of the transporter during colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Some negative findings were published. No association has been found between ABCG2 expression and clinicopathological parameters [ 56 ], or between the expression of ABCG2 protein (basolateral, apical or cytoplasmatic) and age, sex, WHO performance status, location of the primary tumour, number of metastatic sites or liver or lung metastases in colorectal cancer [ 58 ]. Gupta et al [ 26 ] indicated no significant correlation between ABCG2 mRNA level and age, sex, population type, grade, stage or localization, and Halavata et al [ 49 ] reported no connection between ABCG2 expression with the grade, primary localization, T, N, M, age at diagnosis or sex.…”
Section: Discussionmentioning
confidence: 99%
“… Wang et al (2021) reported that ABCG2 rs1871744 and rs4148157 genotype were significantly associated with the poor response in cancer patients receiving platinum-based chemotherapy. Palshof et al (2020) found that colorectal cancer patients with low ABCG2 expression level had a higher chance of obtaining objective response when receiving irinotecan-based treatment. Hence, identifying anticancer drugs that are ABCG2 substrates can be beneficial to the development of clinical treatment strategy and to monitor the occurrence of drug resistance.…”
Section: Introductionmentioning
confidence: 96%